Operando electrodeposition of nonprecious metal copper nanocatalysts on low-dimensional support materials for nitrate reduction reactions - Tan, Shu Fen (2024)
Supported nonprecious metal catalysts such as copper (Cu) are promising replacements for Pt-based catalysts for a wide range of energy-related electrochemical reactions. Direct electrochemical deposition is one of the most straightforward and versatile methods to synthesize supported nonprecious metal catalysts. However, further advancement in the design of supported nonprecious metal catalysts requires a detailed mechanistic understanding of the interplay between kinetics and thermodynamics of the deposition phenomena under realistic reaction conditions. Here, we study the electrodeposition of Cu on carbon nanotubes and graphene derivatives under electrochemical conditions using in situ liquid cell transmission electron microscopy (TEM). By combining real-time imaging, electrochemical measurements, X-ray photoelectron spectroscopy (XPS), and finite-element analysis (FEA), we show that low-dimensional support materials, especially carbon nanotubes, are excellent for generating uniform and finely dispersed platinum group metal-(PGM)-free catalysts under mild electrochemical conditions. The electrodeposited Cu on graphene and carbon nanotubes is also observed to show good electrochemical activity toward nitrate reduction reactions (NO3RRs), further supported by density functional theory (DFT) calculations. Nitrogen doping plays an important role in guiding nonprecious metal deposition, but its low electrical conductivity may give rise to lower NO3RR activity compared to its nondoped analogue. The development of supported nonprecious metals through interfacial and surface engineering for the design of supported catalysts will substantially reduce the demand for precious metals and generate robust catalysts with better durability, thereby presenting opportunities for solving the critical problems in energy storage and electrocatalysis.